(3fRgI GdfahS aj eVMc GdYHhSs - (3GHf ShOhf Ydj GdHTfGhjs
(3ChdgG (B:s
(3GdMeO ddg GdefYe YfO bHV GdfahS HTQM GdUOhQ hcfJ EPG LeYJ ef gPG GdfhY TjFkG TJJ GdfGS Tedg aefge ef jNJdS HYVg hHYVge ef jSQbg LedI Ke LeYJ eG GSJMVQJ s
(3BNQgG (B:s
(3bO LGR ai GdOfjG hai GdBNQI ecGfI de jOf efgG edc Je GdcJGH GdeHGQc HMeO Gddg hYhfg hMSf Jhajbg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1949s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdCOHs